2018
DOI: 10.3389/fmicb.2018.03153
|View full text |Cite
|
Sign up to set email alerts
|

qPCR Assays for the Detection and Quantification of Multiple Paralytic Shellfish Toxin-Producing Species of Alexandrium

Abstract: Paralytic shellfish toxin producing dinoflagellates have negatively impacted the shellfish aquaculture industry worldwide, including in Australia and New Zealand. Morphologically identical cryptic species of dinoflagellates that may differ in toxicity, in particular, species of the former Alexandrium tamarense species complex, co-occur in Australia, as they do in multiple regions in Asia and Europe. To understand the dynamics and the ecological drivers of the growth of each species in the field, accurate quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…qPCR analysis was carried out using assays specific to A. catenella , A. pacificum , and A. australiense [ 31 ]. Species-specific primers were used to identify the species present in the sample ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…qPCR analysis was carried out using assays specific to A. catenella , A. pacificum , and A. australiense [ 31 ]. Species-specific primers were used to identify the species present in the sample ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several qPCR assays for the detection of Alexandrium spp. have been developed based on rRNA genes (e.g., References [216,217,218,219,220,221]), with specificities and sensitivities down to one cell per litre [221]. However, these assays do not provide any indication regarding the potential toxicity of a bloom as they only detect the presence of the Alexandrium cells.…”
Section: Dinoflagellate Toxinsmentioning
confidence: 99%
“…Furthermore, studies have shown that rRNA gene copy numbers are highly variable [216,217,222], and this may lead to over- or underestimation of cell densities [221,223]. Characterization of sxt genes has made the development of PST-producing strain specific qPCR assays [214,215,224,225], and studies have shown that the genomic copy numbers of sxt genes vary less compared to rRNA genes, allowing for more accurate cell density estimates [197,223,224].…”
Section: Dinoflagellate Toxinsmentioning
confidence: 99%
“…By including standard curves of target DNA, the sensitive, qualitative detection is complemented with quantitative estimations of the target organism. Currently, the detection and quantification of toxic microalgae via qPCR has become a standard procedure in many studies and monitoring programs [28][29][30].…”
Section: Introductionmentioning
confidence: 99%